2016
DOI: 10.3390/en9020106
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Bio-Oil from Industrial Food Waste by Liquefied Dimethyl Ether for Biodiesel Production

Abstract: Abstract:The development of new energy sources has become particularly important from the perspective of energy security and environmental protection. Therefore, the utilization of waste resources such as industrial food wastes (IFWs) in energy production is expected. The central research institute of electric power industry (CRIEPI, Tokyo, Japan) has recently developed an energy-saving oil-extraction technique involving the use of liquefied dimethyl ether (DME), which is an environmentally friendly solvent. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Furthermore, the use of edible feedstock for fuel purpose may cause adverse effects on food supply [9][10][11]; therefore, alternative feedstocks must be identified for biodiesel synthesis. Numerous cheap and nonedible feedstocks, including microalgae oil [12][13][14], Jatropha oil [15,16], waste cooking oil [17][18][19], insect fat [20][21][22], Chinese tallow tree seed oil [23], tobacco seed oil [24], sweet basil seed oil [25], Brucea javanica seed oil [26], spent coffee grounds [27], and food waste [28] have been investigated as vital feedstocks for biodiesel synthesis. Two-step transesterification (acid-catalyzed esterification followed by alkali-catalyzed transesterification) is a promising method to produce biodiesel from high free fatty acid oils [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of edible feedstock for fuel purpose may cause adverse effects on food supply [9][10][11]; therefore, alternative feedstocks must be identified for biodiesel synthesis. Numerous cheap and nonedible feedstocks, including microalgae oil [12][13][14], Jatropha oil [15,16], waste cooking oil [17][18][19], insect fat [20][21][22], Chinese tallow tree seed oil [23], tobacco seed oil [24], sweet basil seed oil [25], Brucea javanica seed oil [26], spent coffee grounds [27], and food waste [28] have been investigated as vital feedstocks for biodiesel synthesis. Two-step transesterification (acid-catalyzed esterification followed by alkali-catalyzed transesterification) is a promising method to produce biodiesel from high free fatty acid oils [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The search for newer energy sources to counter the global energy crisis has attained attention in recent years because of energy security and environmental sustainability (Sakuragi, Li, Otaka, & Makino, 2016). This has paved the way for the production of alternate energy sources from the FW which is available in plenty.…”
Section: Bio‐oilmentioning
confidence: 99%
“…Sakuragi et al reported bio‐oil extraction from spent coffee grounds using liquefied dimethyl ether solvent and evaluated its potential as fuel on various parameters such as pour point, kinematic viscosity, and higher heating value, and so forth. The results revealed a maximum oil content (16.8%) which could be used as bio‐oil (Sakuragi et al, 2016). Kostyukevich et al reported a high yield (75%) of bio‐oil from cheese waste by hydrothermal liquefaction (Kostyukevich et al, 2017).…”
Section: Bio‐oilmentioning
confidence: 99%
“…In the most recent studies, the extraction of lipids from soya beans with SC-CO 2 [31] at 300 bar and 50 °C achieved a 6.59% yield. There is only one previous study on the extraction of lipids from soya bean -scum‖ using liquefied DME, which gave a 0.97% yield [32], less than that of SC-CO 2 . However, when the effects of species differences and individual differences are included, it is common for results to be very different, and this comparison cannot be used to judge SC-CO 2 as superior.…”
Section: Introductionmentioning
confidence: 96%